PRODUKTIVITAS DAN RESIKO USAHA PURSE SEINE DI NEGERI LATUHALAT - Pattipeilohy, Robert Frento; Talakua, Eygner Gerald (Program Studi Agrobisnis Perikanan, Universitas Pattimura, 2019)
The decline of small pelagic resources production in Ambon sea waters during a certain season has an impact on the continuity of the purse seine business in Latuhalat Village. This poses a high business risk, given that capture fisheries have different characteristics. This study aims to calculate the productivity and risk of purse seine business in Latuhalat. Survey was conducted to collect primary data to 5 purse seine business owners in Latuhalat as respondents, and productivity calculations were carried out based on comparison of production values ??and total costs, as well as business risk calculations based on probability density. The results showed that the purse seine business in Latuhalat was productive with a value of 1.28 for respondents 1, 2, 3 and 5; and 1.30 for respondents 4 during March to May. The risk of purse seine business in Latuhalat from March to May (west season) is high because each respondent has the potential to experience losses of Rp10,140,219.45 / month, Rp5,906,561.73 / month, Rp5,280,774.25 / month, Rp4. 463,428.57 / month and Rp. 5,173,572,36 / month.